2022
DOI: 10.3389/fcell.2022.983599
|View full text |Cite
|
Sign up to set email alerts
|

NFYA promotes the anti-tumor effects of gluconeogenesis in hepatocellular carcinoma through the regulation of PCK1 expression

Abstract: Reprogramming of glucose metabolism occurs in many human tumor types, and one of these, gluconeogenesis, is known to exhibit anti-tumor effects in hepatocellular carcinoma (HCC). The transcription factor NFYA regulates gluconeogenesis in the normal liver tissue, but the function of the NFYA-gluconeogenesis axis in cancer and the functional differences of NFYA splicing variants in the regulation of gluconeogenesis is still unclear. Here, we demonstrate that NFYAv2, the short-form variant, upregulates the transc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In HCC, the process of glycolysis is often dysregulated and leads to increased glucose consumption and lactate production ( 37 ). Gluconeogenesis then exhibits anti-tumor effects in hepatocellular carcinoma ( 38 ). This study showed that several metabolic pathways were activated in HCC and may plays a significant role in HCC development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, the process of glycolysis is often dysregulated and leads to increased glucose consumption and lactate production ( 37 ). Gluconeogenesis then exhibits anti-tumor effects in hepatocellular carcinoma ( 38 ). This study showed that several metabolic pathways were activated in HCC and may plays a significant role in HCC development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that glucose metabolism disorder is a representative metabolic feature in HCC ( Tsujimoto et al, 2022 ). An increase in the degree of glycolysis in tumors occurs to meet the energy demands of rapidly proliferating tumor cells, and glycolysis can also produce intermediate metabolites supporting the biosynthesis of nucleotides, amino acids, and lipids, thus allowing the rapid proliferation of tumor cells ( Feng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%